LARGE NEUROENDOCRINE TUMOR IN A PATIENT WITH ACROMEGALY CASE REPORT. - Martins, Filadélfia Passos Rodrigues; Oliveira , Leonardo Cesar Silva de; Tavora , Fabio Rocha; Porto , Vitor Camarão; Oliveira , Gabriela Sanford Guimarães Caminha de; Meireles, Victor Sousa Martins de Alcantara (Brazilian Journal of Implantology and Health Sciences, 2023)
The case of a patient with a rare malignancy whose incidence ranges from 0.2 to 2 / 100,000 individuals. The increase in incidence probably showed increasing changes in diagnosis. Approximately 25% of these tumors grow in the lungs and represent 2% of all lung tumors. Of all bronchial NETs, only 5% are associated with multiple type 1 endocrine neoplasms (MEN-1). According to the current WHO classification of 2015, neuroendocrine lung cancer should be classified into typical carcinoids, atypical carcinoids, large cell neuroendocrine carcinoma or small cell carcinoma, the classification being based on histological morphology. The commonly associated endocrine syndromes are inadequate secretion of the natriuretic hormone, Cushing’s syndrome and, rarely, acromegaly. We report a case of a male patient with a large neuroendocrine tumor associated with a pituitary macroadenoma. Laboratory tests on admission were changed, GH of 56.5 ng / mL (Ref <5 ng / mL), IGF-1 of 1304.4 ng / mL (Ref-96.4 - 227.8 ng / mL), chromogranin 4.89 (Ref 3.00), b-HCG-negative. The patient was initially submitted to thoracic surgery and subsequently underwent neurological surgery in another center, so that he was accompanied by professionals from various areas, making it increasingly evident the need for hospitals to have centers for the study of these neuroendocrine tumors.